2008
DOI: 10.1007/s00417-008-0969-2
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal expansion during the water drinking test

Abstract: There was a significant increase of OPA and ChT measurements followed by an IOP rise during the WDT. Increased choroidal volume due to hemodynamic forces may be enrolled in the mechanism of IOP elevation during this stress test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 14 publications
1
32
0
1
Order By: Relevance
“…Similarly, Ehrlich et al [20] did not find a significant difference in peripapillary choroidal thickness in patients with and without open-angle glaucoma using SD-OCT. In agreement with previous investigations [1,2,16,21,22,23,24], we found increased choroidal thickness in glaucomatous eyes versus healthy eyes, which was probably due to vascular events in the uvea that caused the open-angle glaucoma.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Similarly, Ehrlich et al [20] did not find a significant difference in peripapillary choroidal thickness in patients with and without open-angle glaucoma using SD-OCT. In agreement with previous investigations [1,2,16,21,22,23,24], we found increased choroidal thickness in glaucomatous eyes versus healthy eyes, which was probably due to vascular events in the uvea that caused the open-angle glaucoma.…”
Section: Discussionsupporting
confidence: 82%
“…They hypothesized that the reduction in the number of vessels in the choriocapillary would lead to a decrease in the rate of blood flow in a unit of time, and that it would also cause an increase in the gradient of perfusion pressure in the still permeable vessels. An increase in the pressure gradient would lead to a rise in IOP owing to a ductal enlargement and a subsequent increase in the choroidal layer [1,16]. Using B scan echography, De Moraes et al [16] found increased choroidal thickness in glaucomatous eyes during the water drinking test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations